Is the orbit of the exoplanet WASP-43b really decaying? TESS and MuSCAT2 observations confirm no detection. Issue 4 (11th October 2021) - Garai, Z; Pribulla, T; Parviainen, H; Pallé, E; Claret, A; Szigeti, L; Béjar, V J S; Casasayas-Barris, N; Crouzet, N; Fukui, A; Chen, G; Kawauchi, K; et al.
ABSTRACT: Up to now, WASP-12b is the only hot Jupiter confirmed to have a decaying orbit. The case of WASP-43b is still under debate. Recent studies preferred or ruled out the orbital decay scenario, but further precise transit timing observations are needed to definitively confirm or refute the period change of WASP-43b. This possibility is given by the Transiting Exoplanet Survey Satellite ( TESS ) space telescope. In this work, we used the available TESS data, multicolour photometry data obtained with the Multicolor Simultaneous Camera for studying Atmospheres of Transiting exoplanets 2 (MuSCAT2) and literature data to calculate the period change rate of WASP-43b and to improve its precision, and to refine the parameters of the WASP-43 planetary system. Based on the observed-minus-calculated data of 129 mid-transit times in total, covering a time baseline of about 10 yr, we obtained an improved period change rate of $\dot{P} = -0.6 ± 1.2$ ms yr −1 that is consistent with a constant period well within 1σ. We conclude that new TESS and MuSCAT2 observations confirm no detection of WASP-43b orbital decay.